The Dichotomy of Pain and Hope in Bhutanese Nepali Diasporic Poetry - Timalsina, Ramji (Molung Educational Frontier, 2019)
Diaspora is a locale where both the pain and hope work together. The pain of being separated from one’s homeland is compensated with the hope of a better life than that of home back. The creative writings of the diasporas reflect the same dichotomy of pain and hope. This exploratory study on Bhutanese Nepali diasporic poetry displays the same features: the Bhutanese Nepali diasporans have a life full of pain at the loss of their homeland, but they are living with the hope for good life in the days ahead. On the one hand, the trauma they have undergone because of expulsion from their homeland, the experience of being refugees in Nepal for about two decades, and the hardship of transition caused by the third country settlement has been expressed in their poems. On the other hand, their creations show the rays of hope for their life ahead in the host land. They have hopes for a good life, for the preservation of their culture, and real return to Bhutan. In both the themes and styles, many poems simultaneously display both of these aspects of their lives.